Education in the Disruption Era - Fitriani Lubis (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
The disruption era is the occurrence of fundamental changes in all aspects of life. The new system comes to replace the old and obsolete system that is not in accordance with the requirements of the times. In terms of education, disruption will change conventional teaching patterns to digital. The emergence of innovative applications in the world of education can make it easier for everyone to seek knowledge wherever and whenever. The use of social media or online tutoring applications now is greatly benefits for the reach of a wider and more equal audience. This study will discuss the need for our understanding of education in the era of disruption, and how educators deal with this phenomenon with more emphasis on the need for education that can better adapt to current conditions.